2002
DOI: 10.1080/003655102753517217
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of markers of vascular inflammation in patients with coronary heart disease

Abstract: Elevated levels of soluble cell adhesion molecules (sCAMs), inflammatory cytokines and C-reactive protein (CRP) have been associated with atherosclerotic disease states. The aim of the present study was to evaluate whether circulating levels of vascular cell adhesion molecule-1 (sVCAM-1), intercellular adhesion molecule-1 (sICAM-1), E- and P-selectin were significantly elevated in patients with coronary heart disease (CHD) compared with healthy controls, and to study possible associations between these sCAMs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…Several risk factors (ICAM-1, E selectin) were related to cigarette smoking, in agreement with previous studies [28,29]. We have previously reported that smoking cessation reduced levels of ICAM-1 in a subset of this cohort [22], suggesting a causal relation between smoking and ICAM-1 metabolism.…”
Section: Effect Of Diet and Smokingsupporting
confidence: 92%
See 1 more Smart Citation
“…Several risk factors (ICAM-1, E selectin) were related to cigarette smoking, in agreement with previous studies [28,29]. We have previously reported that smoking cessation reduced levels of ICAM-1 in a subset of this cohort [22], suggesting a causal relation between smoking and ICAM-1 metabolism.…”
Section: Effect Of Diet and Smokingsupporting
confidence: 92%
“…Previous studies comparing men and women have largely been conducted in older or diseased individuals [11,26,28,29], although sex differences have been better studied in regard to the more established hemostatic parameters [30]. The prevalence of smoking among the women in our study was surprisingly high, most likely because of their being selected from high-risk families and the prerequisite of dyslipidemia for participation in the study.…”
Section: Effect Of Sexmentioning
confidence: 83%
“…Interleukin (IL)-6, a cytokine known to be secreted from a number of cells including macrophages, lymphocytes and endothelial cells, has been shown to be a major regulator of CRP synthesis and may thus have a key role in initiation of the acute-phase response in various inflammatory conditions such as CVD [11]. In fact, increased levels of IL-6 have been shown to be associated with increased frequency of coronary artery disease (CAD) in men [12], increased risk of myocardial infarction in apparently healthy individuals [13] and to be elevated in patients with CAD compared to healthy controls [14].…”
mentioning
confidence: 99%
“…Soluble forms of these molecules (sCAMs) are thought to reflect the amount of molecules expressed on the endothelial surface [54]. Patients with manifest or future CVD have an elevated serum concentration of these inflammatory markers [55,56]. EPA and DHA supplementation in human studies decrease sCAMs [48,49] and pro-inflammatory cytokines IL-1β, IL-6 and TNFα [50].…”
Section: Biological Effects Of N-3 Fa Related To Cvdmentioning
confidence: 99%